THE EFFECT OF SUSTAINABLE PROCUREMENT ON ORGANIZATIONAL PERFORMANCE IN MANUFACTURING COMPANIES: A CASE STUDY OF NILE BREWERIES LIMITED - Doreck Ambasize (Uganda Christian University, 2024)
The study sought to examine the effects of sustainable procurement on organizational performance in manufacturing companies; a case study of Nile Breweries Limited. The study was guided by three objectives: identifying the specific sustainable procurement practices implemented by Nile Breweries Limited, assessing the extent to which these sustainable procurement practices have influenced the overall organizational performance and establishing the challenges and opportunities associated with implementing sustainable procurement practices for better organizational performance at Nile Breweries Limited. The study was carried out using cross-sectional research design where both quantitative and qualitative research approaches were utilized. Questionnaires were used to collect data from a sample of 108 respondents although 92 of them responded, whereas interviews were conducted with the key informants who are top management of Nile Breweries Limited. The findings revealed that Nile Breweries Limited’s commitment to sustainable procurement practices has significantly advanced its environmental responsibility and financial performance. The company’s proactive approach in sourcing eco-friendly materials, integrating sustainability criteria, and employing lifecycle assessments demonstrates a robust dedication to reducing its environmental impact. This commitment has yielded notable financial benefits through cost savings, enhanced brand image, and increased market share, despite challenges such as high initial costs and limited supplier options. By effectively addressing these challenges and leveraging opportunities for competitive advantage, strategic partnerships, and improved efficiency, Nile Breweries is well-positioned to strengthen its market presence and achieve long-term sustainability goals. Finally, the study recommended the need for Nile Breweries Limited to enhance its investment in sustainable procurement technologies and practices. The study also recommended the need for Nile Breweries Limited to foster stronger partnerships with suppliers who demonstrate a commitment to sustainability. Lastly, the study recommended the need for Nile Breweries Limited to implement comprehensive training programs for both staff and suppliers on sustainable procurement practices.